2006
DOI: 10.1111/j.1365-2214.2006.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal self‐efficacy and maternal perception of child language competence in pre‐school children with a communication disability

Abstract: Background The aim of this study was to describe maternal self-efficacy beliefs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
1
12
2
5
Order By: Relevance
“…From this, it was thought that a logical relationship exists in regard to the significant negative association with STAI: A-trait and the significant positive association with the Mother's Role Attainment Scale showed by the PSESCAMS. "Mothers generally had high self-efficacy beliefs within certain parenting roles, in spite of the fact that their child has a communication disability" (Harty, Alant, & Uys, 2006;p. 144).…”
Section: Criterion-related Validitymentioning
confidence: 99%
“…From this, it was thought that a logical relationship exists in regard to the significant negative association with STAI: A-trait and the significant positive association with the Mother's Role Attainment Scale showed by the PSESCAMS. "Mothers generally had high self-efficacy beliefs within certain parenting roles, in spite of the fact that their child has a communication disability" (Harty, Alant, & Uys, 2006;p. 144).…”
Section: Criterion-related Validitymentioning
confidence: 99%
“…30 In contrast, a study with mothers of school-age children with language disorders found only weak correlations between mothers' self-efficacy and their perceptions of children's communicative competence. 31 Given such conflicting results, more research is needed to clarify the relation between self-efficacy and perceptions among caregivers of children with language disorders.…”
Section: Factors Related To Alignmentmentioning
confidence: 99%
“…A voz humana, embora seja uma função neurofisiológica inata que se aprimora juntamente com o desenvolvimento orgânico do indivíduo, depende de uma complexa atividade de todos os músculos que servem à sua produção, da integridade dos tecidos do aparelho fonador e constitui-se em uma das extensões mais fortes da personalidade 1 Se no adulto os desvios nesse complexo sistema vocal são frequentemente definidos pela própria queixa do falante, na criança eles passam muitas vezes despercebidos aos seus pais e a elas próprias por serem costumeiramente confundidos com sintomas de infecções de vias aéreas superiores ou com qualidade normal da voz. Parece também que pais e educadores são mais atentos a identificar nas crianças problemas de fala e linguagem em detrimento das alterações de voz 2,3 .…”
Section: Introductionunclassified